Making programmer suitable for team-leader: Software team composition based on personality types - Gilal, A.R. (Institute of Electrical and Electronics Engineers Inc., 2016)
The profuse use of software has turned the world into global village where everything is accessible at finger tips. The past studies have confirmed the rapid increase in the demand of software whereas its quality supply has drastically decreased to 6. As high demand and low supply normally generate numerous problems, many researchers, therefore, have raised their concern to develop software affordable, less time consuming and feasible to achieve organisational ends. The findings of the past research studies have determined the fact that besides technical skills, human resources (i.e., personality type for team composition) is of pivotal importance for developing software which has not been seriously addressed. This study has tried to address this prevailing problem by focusing on patterns of personality types of programmer role monitored with team-leader. Additionally, to draw the attention of practitioners, the results are validated with several classification techniques and results appeared with high accuracy. The study has implications on both software developers and researchers having their interest in role of team composition in software development. Â© 2015 IEEE.